Managing the Digital University Paradigms, Leadership, and Organization - Sułkowski, Łukasz (Routledge Open Business and Economics, 2023)
The reflection on university management is based on the question about the shape of universities of the future. Civic, responsible, sustainable, virtual, digital, and many other universities can be mentioned among the concepts present in the literature. All these names describe an important distinctive feature of a university, which will gain more and more importance in the future. However, given the fundamental importance of the radical change taking place, it seems that the most appropriate name, reflecting the essence of the emerging new formation, is ""digital university."" This is because of the importance of digital transformation, which has been developing for several decades, bringing deep and multidirectional changes in the areas of technology, economy, society, and culture. It is a disruptive civilizational transition and, although stretched over many decades, it is revolutionary in nature, significantly changing our lives in the Anthropocene. The book has three cognitive and pragmatic objectives: to provide a new perspective on the changing academic organization and management; to reflect on higher education management concepts and methods; and to present an overview of university management, governance, and leadership, useful from the perspective of academic managers, and other stakeholders.